Technology Entrepreneurship Project (ENT 600) : Techkem Water Sdn. Bhd. / Siti Nur Hatati Shahmizan - Shahmizan, Siti Nur Hatati (2021)
Techkem Water Sdn Bhd is a company based in Malaysia that provide the waste water solution to the society by dedicated a treatment of waste water as part of their service. Considering that all of their service is in aspect of waste water treatment, the company analysis will be focusing on the company service and how the reputation, credibility and productivity of the company affected the service in the term of good or bad. When conducted the SWOT analysis, two problems are detected from the company service that is the coagulant that were used in waste water treatment was not fully green chemistry and usually the waste water treatment plant was prone to produced water pollution from their effluent discharge. Because of this, an orange peel powder product was offered as solution because it has great adsorption capacity to adsorb what coagulant could adsorb in waste water treatment. Not only that, the usage of orange peel powder considered green chemistry as the materials is from biomass waste and reduce the possibility of water pollution due to the less dosage of coagulant used in the process.